Harnessing nature’s arsenal: sustainable plant-based strategies for phytopathogen control - Calefi, Gabriel G.; Silva, Nagela B. S.; Alhatlani, Bader Y.; Abdallah, Emad M.; Martins, Carlos H. G. (Frontiers in Microbiology, 2025)
Phytopathogens represent a persistent threat to global agricultural productivity, precipitating yield losses and destabilizing food security. Conventional reliance on synthetic agrochemicals, while effective in phytopathogen suppression, incurs significant economic burdens, drives environmental toxicity, and accelerates the evolution of resistant microbial strains, with collateral risks to ecosystem integrity and public health. This review synthesizes current advancements in harnessing plant- and microorganism-derived extracts, bioactivity-guided fractions, and purified phytochemicals as eco-compatible antimicrobial agents against phytopathogenic bacteria and fungi. Furthermore, we propose a novel framework for standardized prioritization of natural products, integrating efficacy thresholds, phytochemical complexity, and mechanistic specificity to guide scalable antimicrobial discovery. Meta-analysis of published studies reveals a predominant focus on Fusarium spp. as model phytopathogens, with dilution in broth and agar diffusion as the predominant in vitro assays. Quantitative benchmarks for antimicrobial potential were established: bacterial Minimum Inhibitory Concentrations (MICs) ≤ 2.5 mg/mL (crude extracts), ≤0.6 mg/mL (fractions), and ≤64 μg/mL (purified compounds), alongside fungal growth inhibition thresholds <52% (agar dilution assays). These criteria highlight the differential bioactivity of natural product tiers, emphasizing the role of compound purification in potency enhancement. By bridging phytochemical innovation with agronomic applicability, this work positions plant-derived antimicrobials as pivotal tools for sustainable disease management, circumventing agrochemical limitations while advancing One Health-aligned agricultural practices.